Is α-Tocopherol or Sodium Ascorbate Effective as Antioxidant on Fracture Resistance of Bleached Teeth? - Leandrin, Thais P. [UNESP] (2020)
AIM: To evaluate the effect of two antioxidant formulations (sodium ascorbate and α-tocopherol) on fracture resistance of endodontically treated teeth. MATERIALS AND METHODS: Sixty human premolars were endodontically treated and divided into six groups (n = 10): G1 (negative control)-unbleached and restored with composite resin; G2 (positive control)-bleached in three sessions, using hydrogen peroxide (15 H2O2) plus titanium dioxide (TiO2) nanoparticles, photoactivated by LED laser system and restored with composite resin; G3-bleaching similar to G2, after the use of 10% sodium ascorbate gel for 24 hours and restored with composite resin; G4-similar to G3, but with the use of 10% sodium ascorbate solution and restored with composite resin; G5 and G6-similar to G3, but with the use of 10% α-tocopherol in alcohol or carbopol, respectively, and was also restored. A mechanical fracture resistance test was performed and the Kruskal-Wallis test was used to evaluate the results (α = 0.05). RESULTS: No statistical difference was observed in fracture resistance between groups (p > 0.05). Regarding the antioxidant and pharmaceutical formulation applied, no statistical difference was detected in any comparison (p > 0.05). The frequency of fractures considered favorable was higher in G1 and G3 compared to the other groups. CONCLUSION: The endodontically treated teeth bleached with 15 H2O2 plus TiO2 nanoparticles and photoactivated with the LED laser did not decrease the fracture resistance and the use of sodium ascorbate or α-tocopherol did not increase the crown fracture resistance. CLINICAL SIGNIFICANCE: The literature reports a significant reduction in the bond strength of restorations on the bleached dentin. Therefore, the use of antioxidant agents may have a promising effect on fracture resistance of endodontically treated teeth.